Стратегія мінімізації небажаних складових миттєвої потужності із застосуванням різних топологій паралельних активних фільтрів - Михальський, В.М.; Соболєв, В.М.; Чопик, В.В.; Шаповал, І.А. (Технічна електродинаміка, 2014)
Розглянуто сукупність складових миттєвої потужності, які відображає p-q-r теорія. Наведено основні умови появи та можливості компенсації небажаних складових миттєвої потужності за допомогою різних топологій паралельних активних фільтрів. Отримано співвідношення, які забезпечують спрощений розрахунок струмів компенсатора без застосування перетворень координат. Рассмотрена совокупность составляющих мгновенной мощности, которые отображает p-q-r теория. Приведены основные условия появления и возможности компенсации нежелательных составляющих мгновенной мощности с помощью разных топологий параллельных активных фильтров. Получены соотношения, которые обеспечивают упрощенный расчет токов компенсатора без применения преобразований координат. The aim of the paper is to develop strategy of direct calculations of compensation currents of the shunt active filter with different topologies for minimization of undesirable instantaneous power components. The set of instantaneous power components, which p-q-r theory represents, has been considered. Basic conditions for the appearance and possibilities of compensation of undesirable components of instantaneous power using different topologies of shunt active filter have been presented. The topological differences between the three-phase three-wire and three-phase four-wire systems (with and without energy storage) have been considered. Calculation strategy of compensation currents which is consistent with the goal of minimization of undesirable instantaneous power components has been studied. Ratios which provide a simplified calculation of compensator currents without the use of coordinate transformations have been obtained. Simulation results confirm the applicability of the obtained mathematical approaches to calculate the compensator currents. Qualitative differences in the application of expressions for calculation of currents in different conditions have been determined. Boundaries of correct adjustment of instantaneous power components to form undistorted network currents have been defined.